Vitamin D deficiency in elderly: Risk factors and drugs impact on vitamin D status - Kweder, Hasan; Eidi, Housam (Avicenna Journal of Medicine, 2018)
Introduction: Vitamin D (VD) deficiency is a major public health problem worldwide. In spite of its high prevalence, particularly among elderly people, VD deficiency is still underestimated by many physicians. Increasingly, VD deficiency is associated with several known geriatric syndromes. Methods: The study sample consisted of 125 patients, aged 75 years and older, admitted to the acute geriatric unit. The plausible association between the serum 25-hydroxyvitamin D [25(OH)D] level and patient age, sex, body mass index, renal function, cholecystectomy history, and the prescribed drugs had been investigated. The Fisher's exact test was used to conduct the statistical analysis of data. Results: Surprisingly, furosemide treatment was correlated with normal 25(OH)D levels and an increased incidence of secondary hyperparathyroidism. Unlike the other four parameters mentioned above, our data showed that only the patient sex exhibited a significant association with 25(OH)D level as elderly males suffered from a serious VD deficiency as compared to elderly females. Conclusion: Old age is an independent risk factor for VD deficiency. The supplementary dose of VD should be precisely defined to achieve the optimal serum 25(OH)D level in elderly people. The definition of the normal serum 25(OH)D threshold in elderly furosemide-treated patients is worth of further studies.
Keywords: Furosemide; geriatrics; Vitamin D deficiency